Misses in "Hot Hand" research - Arkes, J. (Journal of Sports Economics, 2013)
Until recently, no study has found evidence for the "hot hand" in the National Basketball Association. Thus, many researchers have claimed that the hot hand and momentum effects are myths. This article presents simulations that demonstrate how the primary methods for estimating the hot hand effect understate the effect and have a low chance of detecting significance and that the infrequency of the hot hand contributes to the understated estimates and the inability of tests to detect significance. These results suggest that recent research showing a small hot hand effect for free throws is indicative of a much larger hot hand effect.